Kenotična književnost in vprašanje sebstva - Ciglenečki, Jan (Primerjalna književnost, 2018)
The focus of the present article is early Byzantine literature, especially the segment of it which can be designated kenotic literature. Two eminent early Byzantine works are exposed: Mystical Theology by Dionysius the Areopagite and The Ladder of Divine Ascent by John Climacus. The syntagm kenotic literature can delineate religious and mystical texts, characterized by the gradual progress from "outer" layers of the self to the fundamental dimensions of human being on the path to God. Phenomenologically, we discern two types of selfhood: on one side there is basic, core or minimal self, which constitutes the basis of experiencing oneself and the feeling, that it is me, who is experiencing certain experience, and on the other side narrative or extended self, which unfolds who is that me and how do I feel myself extended in time, what is my life story, how do I differ from others, and what are my characteristics. In mystical tradition, another horizon of selfhood is opened. Attentive and incessant prayer leads a monk to perceive and differentiate various mental states and with that various levels of selfhood. In that process, there is the potential for gradual abandoning attachment to particular parts of narrative self, which function as disturbances in the form of thoughts, ideas, emotions, wishes, temptations, and fears. Abandoning the attachment to the narrative layers of selfhood leads to emptying of oneself, which is known in Christian monastic tradition as kenosis. That is why all the processes leading toward emptying of self are called kenotic processes and the attained self kenotic or mystical. Kenotic literature functions as a guide on the path of emptying the self.
Keywords: Dionysius Areopagita, svetnik, 5./6. st.; literature and religion; Johannes Climacus, svetnik, ok. 575-ok. 650; Byzantine monasticism; literatura in religija; mysticism; mystical experience; bizantinsko meništvo; self; mistika; mistično izkustvo; prayer; sebstvo; kenosis; kenotic literature; molitev; kenoza; kenotična književnost